Računsko sodišče in institut exceptio illegalis - Bedič, Matevž (Podjetje in delo, 2024)
This paper discusses the (im)possibility of using the exceptio illegalis institution in audit procedures conducted by the Court of Audit. The exceptio illegalis institution is defined in Article 125 of the Slovenian Constitution, which states that judges are independent and bound by the Constitution and the law. This wording corresponds to Article 150(3) of the Constitution, which grants the Court of Audit independence in accordance with the Constitution and the law. Even though the Court of Audit does not belong to any of the three classical branches of government, it significantly strengthens the separation of powers. The exceptio illegalis institution also reinforces the principle of the separation of powers between the judiciary and the executive. Notwithstanding certain indications (such as the name, the grammatical interpretation of Article 150(3) of the Constitution) that could grant the exceptio illegalis institution to the Court of Audit, this paper rejects such a possibility. After an introductory outline of the basic concepts, three arguments are raised to reject the use the exceptio illegalis institution in audit procedures. Firstly, the Court of Audit is not a part of the judiciary; secondly, it does not issue individual acts; and thirdly, the Court of Audit can file a request for the review of constitutionality and legality of regulations before the Constitutional Court.
Keywords: Računska sodišča